1993
DOI: 10.1093/ije/22.4.644
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity at Work and Cardiovascular Disease Risk: Results from the MONICA Augsburg Study

Abstract: In the MONICA Augsburg study the relationship between physical activity at work, cardiovascular risk factors, incidence of fatal and non-fatal myocardial infarction (MI) and total mortality was investigated in employed men. The MONICA Augsburg baseline survey of 1984/85 was designed as a cross-sectional study with follow-up. Physical activity was determined in 45-64 year old men by interview (n = 1074, 83.6%) and by a 7-day activity diary (n = 797, 62.0%). Employed men were categorized into an active versus in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 0 publications
7
45
1
1
Order By: Relevance
“…5 Education, age and body weight are important factors influencing accuracy of physical activity estimations. 4,28,29 It has also been shown that subject compliance is a key limiting factor in the use of physical activity records. 5 For physical activity records, correlation coefficients between 0.6 and 0.8 and a mean difference of 7.9% have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…5 Education, age and body weight are important factors influencing accuracy of physical activity estimations. 4,28,29 It has also been shown that subject compliance is a key limiting factor in the use of physical activity records. 5 For physical activity records, correlation coefficients between 0.6 and 0.8 and a mean difference of 7.9% have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have focused on all-cause or CVD mortality and morbidity rates or cardiovascular event incidence rates in relation to work 19,22,41 or LTPA. 12,15,18,19,22,41,42 Some studies have also investigated the combined effects of work and LTPA.…”
Section: Discussionmentioning
confidence: 99%
“…12,15,18,19,22,41,42 Some studies have also investigated the combined effects of work and LTPA. 13,14,16,17,20,21 In those previous studies, body composition was reported as a contributing variable rather than the major variable of interest.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 A Japanese prospective cohort study has shown that walking to work and other leisure time physical activity decreased the risk for hypertension in Japanese men. 36 Several population studies have demonstrated an inverse relationship between leisure time physical activity and BP levels.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%